Pelatihan Akuisisi Data Geolistrik Dalam Identifikasi Subsurface di SMK Penerbangan Techno Terapan - Emi Prasetyawati Umar; Alfian Nawir; Agriani Pongkessu; Aryadi Nurfalaq; Rahma Hi Manrulu; Muhammad Adam Marnas (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
School partners indicated that there were several problems, namely that there were still students who did not understand how to interpret resistivity geoelectrical data. This is due to the limited facilities and infrastructure as well as teaching staff in supporting the learning process in schools. The purpose of this PkM is to prepare students' abilities as early as possible so that they can understand how to interpret resistivity geoelectrical data before entering the world of work in geology and mining. Another thing is that school partners can more easily and effectively teach the interpretation of resistivity data using the geoelectric method in the teaching and learning process in schools.. The method used in achieving the objectives is a questionnaire (pretest and posttest) with descriptive statistical analysis, lectures (presentations) and discussions as well as field practice. The results of the analysis showed an increase in students' ability in the acquisition of geoelectric resistivity data after attending the training. Prior to participating in the training, 70% of students had the ability to acquire geoelectric resistivity data in the Poor category. However, after participating in the training, the students' abilities increased to Excellent (55%).